(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate the cyclic fatigue resistance of novel NiTi files (subjected to heat treatment) using the in vitro model (artificial canal). Twelve ProDesign Logic instruments - PDL 25/.06 (Easy Equipamentos Odontológicos, Belo Horizonte, Brazil) and 12 Protaper Next X2 instruments - PTN (tip 25) were included in this research. The Static cyclic fatigue test was performed with a grooved stainless steel block simulating a canal of 1,5 mm diameters, a 60o angle of curvature and 5 mm radius. The files were positioned inside the artificial canal and rotated until the fracture occurred. Using the time until fracture (seconds) and the number of rotations per minute (RPM), the number of cycles until fracture (NCF) was calculated and the length of ruptured fragments was registered. Three samples from each group were analyzed in Scanning Electronic Microscopy (SEM) to characterize the metal rupture. Data were analyzed using the Mann-Whitney non-parametric test and the level of significance considered was p<0.05. PDL obtained a mean value of 956,0 NCF (352,0 - SD) and PTN achieved 391,0 NCF (36.7 - SD) with statistical significance between the groups (p < 0.001). There was no statistical difference on fragment length (p > 0.05). SEM analysis showed features compatible with ductile fracture. ProDesign LOGIC files showed higher NCF than Protaper Next X2. There was no difference between groups considering the length of the ruptured fragment.